PENGARUH KEPEMIMPINAN, BUDAYA ORGANISASI DAN KOMITMEN ORGANISASIONAL TERHADAP KEPUASAN KERJA GURU SMKN 1 KLEGO BOYOLALI - Trishananto, Yudha -; Suseno, Y Djoko (Universitas Slamet Riyadi, 2013)
This reasearch purpose to analyze the significant of impact: 1). leadership variable to job satisfaction, 2). organization practice variable to job satisfaction, 3). organizational commitment variable to job satisfaction, 4). The dominant variable that have impact to job satisfaction. Population of this reasearch are 60 teachers in SMKN 1 Klego. The sample of this reasearch are 60 teachers with sampling technique is sensus methode. To collecting data used quesionnaire technique with validity and relliability. The data analyzed methode used double regression linear with classic assumption. Analyzed result showed: 1). The same regression value of leadership is 0,395; value of organization practice is 0,219; value of organizational commitment is 0,197, 2). Result of variable t test significant value of leadership is 0,005 < 0,05; significant value of organization practice is 0,213 > 0,05; significant value of organizational commitment is 0,251 > 0,05, so the conclussion is variable that have possitive impact and significant to job satisfaction is leadership variable, for organization practice and organizational commitment variable have possitive impact but is not significant to job satisfaction. Result of determination coefissien test R2 is 0,410, it means impact of leadership, organization practice, and organizational commitment to job satisfaction is 41 percent, more than it’s impact of the others variable. Keywords: leadership, organization practice, organizational commitment, job satisfaction.